2016
DOI: 10.1155/2016/4980251
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Serum Myeloid-Related Protein-8/14 and Eosinophil Cationic Protein in Patients with Coronary Artery Disease

Abstract: Objective. To investigate the changes in serum Myeloid-Related Protein 8/14 (MRP8/14) and Eosinophil Cationic Protein (ECP) levels in patients with different types of coronary artery diseases (CAD) and assess the value of MRP8/14 and ECP detection in predicting CAD. Methods. 178 patients were divided into CAD group including unstable angina pectoris (UAP), acute myocardial infarction (AMI), and stable angina pectoris (SAP). Thirty-six individuals with normal coronary artery served as the control group. Serum M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…It was shown that the expression of S100A8/A9 was high in human atherosclerotic lesions and the blood levels were also increased in the patients with coronary artery diseases (CAD), which implied S100A8/A9 might act as a biomarker for cardiovascular events ( 143 ). Recent research has shown similar findings that serum S100A8/A9 levels were elevated in 178 CAD patients with unstable angina pectoris or acute myocardial infarction, and the level of S100A8/A9 was significantly positively linked with CRP ( P < 0.01) ( 144 ). These clinical data suggest that S100A8/A9 may become a novel biomarker for CAD ( 139 ).…”
Section: S100 Proteins As Biomarkers In Specific Diseasesmentioning
confidence: 64%
“…It was shown that the expression of S100A8/A9 was high in human atherosclerotic lesions and the blood levels were also increased in the patients with coronary artery diseases (CAD), which implied S100A8/A9 might act as a biomarker for cardiovascular events ( 143 ). Recent research has shown similar findings that serum S100A8/A9 levels were elevated in 178 CAD patients with unstable angina pectoris or acute myocardial infarction, and the level of S100A8/A9 was significantly positively linked with CRP ( P < 0.01) ( 144 ). These clinical data suggest that S100A8/A9 may become a novel biomarker for CAD ( 139 ).…”
Section: S100 Proteins As Biomarkers In Specific Diseasesmentioning
confidence: 64%
“…ECP, a marker of eosinophil activity, is released by cell degranulation and participates in the activation of the coagulation cascade. It has been previously reported that ECP can increase in the whole spectrum of stable and unstable ischemic heart disease [ 27 , 28 ]. In STEMI patients we detected raised ECP levels upon patient arrival that returned to control levels 1 month post-reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils are also implicated in atherosclerosis. The plasma levels of eosinophil cationic protein are positively correlated with the extent of atherosclerosis in patients with coronary artery disease 167 , 168 . The eosinophil chemokine eotaxin (also known as CCL11) is highly expressed in human atherosclerotic plaques 169 – 171 .…”
Section: Thromboinflammation and Cardiovascular Eventsmentioning
confidence: 99%